التأثيرات الفيتوكيميائية و البيولوجية للمستخلص الإيثانولي لثمار نباتي الخرب و البلوط : Certonia siliqua ، Quercus ilex - مفتاح, وفاء; بن علي, عائشة (Université of Eloued, 2019)
This study aimed to evaluate the nutritional value, phytochemical and antioxidant capacity of Ceratonia siliqua and Quercuse ilex for unripe stage (green) and Ripe stage (brown). Concerning Ceratonia siliqua, the yield was 7...2% and 2.0.7%, The nutritional value showed that the carbohydrates ratio was .542.mg/g and 52492 mg/g, the proteins was 249mg/g and.429 mg/g, the lipids was 52.2. mg / g and 9..33 mg/g for unripe stage (green pods) and the ripe stage (brown pods) respectively. The total phenols were 382.52μg EAG/mg and 448.437μg EAG/mg, Flavonoids content was 101.29 μg EQu/mg and 0,044 EQu/mg , the tannins hydrolysable and tannins condensed wer (78480μgEAT/mg and 22.47 μgEAT/m,212.5 μgECA/mg and 109.5 μgECA/mg) for unripe stage (green pods) and the ripe stage (brown pods) respectively. C.siliqua fruits showed a good antioxidant activity for the unripe fruits with an IC50 17.171 μg/ml and high antioxidant activity in ripe fruits with an IC50 1.70 μg/ml . The inhibition rate was 93.29% at 100μg/ml for unripe stage and 87.30% at 400μg/ml in the ripe stage fruits. Concerning Quercuse ilex, the yield was 17.99 % and 13.42%, the nutritional value showed that the carbohydrates ratio was 25.01mg/g and 30.3 mg/g, the proteins was 11.42 mg/g and 13.36 mg/g, the lipids was 10.28 mg / g and 17.1 mg/g for the unripe stage and ripe stage respectively. The total phenols were 519.33μg EAG/mg and 474.5μg EAG/mg, Flavonoids content was 5.037 μg EQu/mg and 4. 592 EQu/mg, the tannins hydrolysable and tannins condensed were (39.454μgEAT/mg and 16.92 μgEAT/m, 149.5 μgECA/mg and 90.5 μgECA/mg) for the unripe stage (green pods) and ripe stage (brown pods) respectively. Q.ilex fruits showed a good activity for the unripe fruits with an IC50 1.866 μg/ml and high antioxidant activity in ripe fruits with IC50= 1.734 μg/ml . The inhibition rate was 94.78% at 400μg/ml for unripe stage and 99.08% in the ripe stage fruits. The antimicrobial activity showed that there was no effect of all the extracts on the strains tested.
Biologie et Valorisation des Plantes
Keywords: الخروب ، البلوط; Certonia siliqua ، Quercus ilex